2012
DOI: 10.7448/ias.15.2.17381
|View full text |Cite
|
Sign up to set email alerts
|

Community adherence support improves programme retention in children on antiretroviral treatment: a multicentre cohort study in South Africa

Abstract: BackgroundHIV-positive children in low-income settings face many challenges to adherence to antiretroviral treatment (ART) and have increased mortality on treatment compared to children in developed countries. Adult ART programmes have demonstrated benefit from community support to improve treatment outcomes; however, there are no empirical data on the effectiveness of this intervention in children. This study compared clinical, virological and immunological outcomes between children who received and who did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
69
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 25 publications
11
69
0
Order By: Relevance
“…The effect of health worker towards HIV/ AIDS countermeasure behavior Path analysis result in the study showed that health worker support had direct and positive relations towards HIV countermeasure behavior, even though it was statistically insignificant. This was supported by the study done by Grimwood et al, (2012), that shows that supports from health worker will improve PLWHA health status.…”
Section: The Effect Of Family Supportmentioning
confidence: 66%
“…The effect of health worker towards HIV/ AIDS countermeasure behavior Path analysis result in the study showed that health worker support had direct and positive relations towards HIV countermeasure behavior, even though it was statistically insignificant. This was supported by the study done by Grimwood et al, (2012), that shows that supports from health worker will improve PLWHA health status.…”
Section: The Effect Of Family Supportmentioning
confidence: 66%
“…CBAS likely retains a larger pool of patients at increased risk of having unsuppressed viral loads by reducing mortality and LTFU amongst higherrisk children Grimwood et al, 2012). OT analyses are thus likely biased in the estimation of the true effect of CBAS on virological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, community adherence support has been shown to improve retention in care of children on ART in the SA public sector and should be considered for caregivers of children down-referred to community clinics on ART. [18] …”
Section: Discussionmentioning
confidence: 99%